KANDUNGAN NILAI DALAM PEMBELAJARAN BIOLOGI SMA TENTANG AKSI-INTERAKSI ORGANISME - SUYATI, SUYATI (FOUNDASIA, 2005)
Learning is an activity to prepare learners to develop their potentials so that they are able to live the life. For the learning to take place to the optimunt a good preparation and a good plan are necessary in order that learning materials, including their carry-over effects are meaningful and prepare learners' life. The carry-over effects of the learning of organism action interaction at senior high schools are related to the necessity of conducting education with individual and social values. Individual values such as persistence, hard work, courage, creativity, logic, activeness and productiveness, tolerance, and intelligence determine the choice. Social values imply that in society there are different types of human being with different characteristics. Therefore, it is necessary jor human beings to know and understand each other to create a balance in order to attain ideals in life.